ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL DISCLOSURE TERHADAP EARNING RESPONSE COEFFICIENT (Studi Pada Perbankan Yang Listed di Bursa Negara ASEAN Tahun 2015-2016) - Erwindiawan , (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2019)
This study aims to determine the effect of Good Corporate Governance and Intellectual Capital Disclosure as independent variable on Earning Response Coefficient??as dependent variable with control variable Size, Leverage??and Growth.The populations in this research were banking??sector companies in ASEAN (Indonesia, Singapura, Malaysia, Thailand and Philipine) and ASEAN CG Scorecard assesment in the period 2015-2016. By using purpose sampling??method obtained 73 sample. The method used in this study is causal research methods and from 73 banking companies are used as the samples of this study with the specified criteria. The statistical method being used is multiple linear regression with SPSS software. The result??shows??that??: 1) Good corporate governance has effect on Earning Response Coefficient, 2) Intellectual Capital Disclosure has effect on Earning Response Coefficient.